THE INFLUENCE OF SOCIAL MEDIA ON LEARNING STYLE OF STUDENTS’ IN COLLEGES OF EDUCATION IN KWARA STATE, NIGERIA - Aderonke Kofo Soetan; Ajayi Samuel Ololade; Amos Ochayi Onojah; Adenike Janet Aderogba (Indonesian Journal of Learning and Instruction, 2020)
Social media is a platform which enables users to connect, create account profile, share files and interact with other users on the same platform. There have been reports that interaction of people with the social media has resulted to change in their behavior. However, it is not known whether or not this social media platform has capacity to influence learners’ behavior particularly their learning style. This research examined the influence of social media on Colleges of Education students’ learning style in Kwara State. Simple random sampling technique was employed to drawn 220 students (114 male and 106 female) from the selected Colleges of Education in Ilorin, Kwara State. Four (4) research questions were raised and answered using frequency count and percentage while t-test was used to analyze the only hypothesis. The findings showed that social media had influence on Colleges of Education students’ learning style with 36.4 and there was no significant difference in the influence of social media on learning style based on gender with 0.592 P. (0.253). Based on the findings,  it was recommended that the use of social media for teaching in Colleges of Education be encouraged for interaction between instructors and student teachers to foster learning under close monitoring.Keywords: colleges of education influence; learning style; social media; students.